1991
DOI: 10.5642/aliso.19911301.06
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Evolution of Forms and Types of Sieve-element Plastids in the Dicotyledons

Abstract: Sieve-element plastids may contain any combination of protein crystals (c), protein filaments (f), and starch grains (s), or none of these. All structurally distinct combinations (=forms) possible (s, cs, cfs, c, cf, fs, f, o) are recorded among the 2100 dicotyledons investigated so far with the transmission electron microscope (representing 381 of more than 460 families described). The six forms that include c and/or f define the P-type and are found in some 620 species, mainly confined to Magnolianae, Caryop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 7 publications
0
36
0
2
Order By: Relevance
“…However, such plastids have been identified in the sieve elements and companion cells that comprise phloem. 49,50 Promoter-GUS fusions used in this study revealed that PHT4;3 and PHT4;5 were expressed in the phloem tissue of leaves and cotyledons, but not roots. Expression of both PHT4;3 and PHT4;5 in leaves was diurnal with transcripts more abundant in the light.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such plastids have been identified in the sieve elements and companion cells that comprise phloem. 49,50 Promoter-GUS fusions used in this study revealed that PHT4;3 and PHT4;5 were expressed in the phloem tissue of leaves and cotyledons, but not roots. Expression of both PHT4;3 and PHT4;5 in leaves was diurnal with transcripts more abundant in the light.…”
Section: Methodsmentioning
confidence: 99%
“…Little has been reported on the metabolic functions of phloem plastids, although they may be the primary sites of tryptophan biosynthesis, 51 and at least some of these plastids accumulate starch. 50 Given that amino acid and starch synthesis are ATP consuming and Pi liberating processes, we hypothesize that PHT4;3 and PHT4;5 contribute to Pi export from phloem plastids.…”
Section: Methodsmentioning
confidence: 99%
“…In allen Familien der Spermatophyten findet man Plastiden in den Siebelementen [3]. Ihre Ultrastruktur ist sehr unterschiedlich, aber familienspezifisch.…”
Section: Organelle Der Siebelementeunclassified
“…What remains at maturity is the plasma membrane, a thin layer of parietal cytoplasm composed of stacked ER or fenestrated ER (Thorsch and Esau 1981a,b;Sjolund and Shih 1983) and a few dilated mitochondria (Evert 1990). Phloem-specific plastids of two types, with proteinaceous (P-type plastids) or starch (S-type plastids) inclusions (Esau 1969;Behnke 1991a;van Bel and Knoblauch 2000;van Bel 2003), and SE phloem proteins (Eleftheriou 1990;Evert 1990;Cronshaw and Sabnis 1990;Behnke 1991b;Iqbal 1995) are also conspicuous in the SE. To prevent these organelles being dragged along in the turbulent mass flow within the SE, 7-nm-long macromolecular extensions anchor the ER, mitochondria and plastids to each other and to the plasma membrane (Ehlers et al 2000).…”
Section: The Specialised Case Of Pore-plasmodesma Unitsmentioning
confidence: 99%